ANALYSIS OF MIGRANTS’ COMPETITIVENESS IN INDONESIA - Harlen; Pailis E.A.; Karneli O. (Russian Journal of Agricultural and Socio-Economic Sciences, 2017)
This study was conducted to investigate and analyze the influence of skills toward migrants’ competitiveness and the influence of wisdom toward migrants’ competitiveness in Pekanbaru, the capital city of Riau Province, Indonesia. This study employed a quantitative approach in the form of survey. There were 125 migrants who participated in this study who were chosen using quota sampling technique based on the classification of migrants’ activities. The first finding shows that there is a significant influence between migrants’ skills and their competitiveness. Secondly, migrants’ wisdom has certain positive yet insignificant influence toward their competitiveness. The results of this study also show that migrants’ competitiveness has been satisfying. Migrants are also known to have strong basic characteristics to achieve certain target or to reach their success.